Effective decellularisation of human saphenous veins for biocompatible arterial tissue engineering applications: Bench optimisation and feasibility in vivo testing. (March 2021) - Sulaiman, Nadiah S; Bond, Andrew R; Bruno, Vito D; Joseph, John; Johnson, Jason L; Suleiman, M-Saadeh; George, Sarah J; Ascione, Raimondo
Human saphenous vein (hSV) and synthetic grafts are commonly used conduits in vascular grafting, despite high failure rates. Decellularising hSVs (D-hSVs) to produce vascular scaffolds might be an effective alternative. We assessed the effectiveness of a detergent-based method using 0% to 1% sodium dodecyl sulphate (SDS) to decellularise hSV. Decellularisation effectiveness was measured in vitro by nuclear counting, DNA content, residual cell viability, extracellular matrix integrity and mechanical strength. Cytotoxicity was assessed on human and porcine cells. The most effective SDS concentration was used to prepare D-hSV grafts that underwent preliminary in vivo testing using a porcine carotid artery replacement model. Effective decellularisation was achieved with 0.01% SDS, and D-hSVs were biocompatible after seeding. In vivo xeno-transplantation confirmed excellent mechanical strength and biocompatibility with recruitment of host cells without mechanical failure, and a 50% patency rate at 4-weeks. We have developed a simple biocompatible methodology to effectively decellularise hSVs. This could enhance vascular tissue engineering toward future clinical applications.